ChemInform Abstract: Stereoselective Monoamine Oxidase‐Catalyzed Oxidative Aza‐Friedel—Crafts Reactions of meso‐Pyrrolidines in Aqueous Buffer. Issue 39 (September 2016) - de Graaff, Corien; Oppelaar, Barry; Peruch, Olivier; Vande Velde, Christophe M. L.; Bechi, Beatrice; Turner, Nicholas J.; Ruijter, Eelco; Orru, Romano V. A.
Abstract: An one‐pot chemoenzymatic oxidative aza‐Friedel—Crafts reaction for the direct α‐functionalization of pyrrolidines including both secondary as well as tertiary amines is developed.